Employment prospects after completing vocational training in Germany from 2008-2014 : a comprehensive analysis - Dummert, Sandra [Verfasser] (My University, 2021)
"The transition from vocational education and training to regular employment is an important step in the occupational biography of apprenticeship graduates. In the last decade, the retention rate of apprenticeship completers has remained stable at a high level, and graduates face good job opportunities in Germany. Despite these positive circumstances, not all apprenticeship graduates succeed in the direct transition from vocational training to regular employment and are affected by unemployment. My paper offers deeper insights into training establishment-specific, individual and external regional characteristics that influence the transition process at this crucial point in the employment career. I consider the employment status of apprenticeship graduates by estimating multinomial logit models at three time points after the end of training, namely, one month and one and two years later. Using linked employer-employee data, I find evidence not only that sociodemographic characteristics and training establishment-specific determinants affect the transition at the second threshold but also that regional factors influence the probability of becoming unemployed or remaining with the training establishment after the end of the apprenticeship." (Author's abstract ; BIBB-Doku)
Keywords: G 1.3.2.2 Übergänge; G 1.3.2.2.3 Zweite Schwelle, in Arbeit; 370; Berufsbildung; Berufseinmündung; Zweite Schwelle; Regionale Faktoren; Betriebsgröße